2009
DOI: 10.1007/s11605-008-0699-0
|View full text |Cite
|
Sign up to set email alerts
|

Pleuropancreatic Fistulae: Specialist Center Management

Abstract: Pleuropancreatic fistulae can present a challenging diagnostic dilemma. A multi-disciplinary approach addressing nutritional support and endotherapy allows successful non-operative resolution within specialist units.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…ERCP with pancreatic stent placement results in resolution of PPF in majority of the cases. 4 In our patient, ERCP was not possible because of the duodenal stenosis. Surgery is used if stent placement and/or medical therapy fails and usually includes distal pancreatectomy or pancreatojejunostomy.…”
Section: Discussionmentioning
confidence: 68%
“…ERCP with pancreatic stent placement results in resolution of PPF in majority of the cases. 4 In our patient, ERCP was not possible because of the duodenal stenosis. Surgery is used if stent placement and/or medical therapy fails and usually includes distal pancreatectomy or pancreatojejunostomy.…”
Section: Discussionmentioning
confidence: 68%
“…Some reports have shown that the diagnostic sensitivity of MRCP is almost the same as that of ERCP and is higher than that of CT [21][22][23] . Our previous report found that a precise assessment of the pancreatic ductal system is essential for effectively managing patients with IPF; MRCP can be a promising tool for evaluating the pancreatic duct system, and it is also helpful for selecting the optimal treatment strategy 24) .…”
Section: Discussionmentioning
confidence: 95%
“…Strictures are treated by dilatation, followed by stenting with plastic stents or a fully covered self‐expanding metal stent . The success rate of ERCP in treating ductal disruptions and pancreatic effusions is between 55% and 100% …”
Section: Discussionmentioning
confidence: 99%